Duckweed protein: extraction, modification, and potential application - Nurul Shaeera Sulaiman; Hana Mohd Zaini; Wan Rosli Wan Ishak; Patricia Matanjun; Ramlah George @ Mohd. Rosli; Sylvester Mantihal; Ching Fui Fui @ Faihana Ching Abdullah; Wolyna Pindi (Elsevier Ltd., 2025)
Discovering alternative protein sources that are both nutritious and environmentally friendly is essential to meet the growing global population’s needs. Duckweed offers promise due to its cosmopolitan distribution, rapid growth, high protein content, and scalability from household tanks to large lagoons without requiring arable land that competes for the major crops. Rich in essential amino acids, particularly branched-chain amino acids, duckweed supports human health. Extraction methods, such as ultrasound and enzymatic techniques, enhance protein yield compared to traditional methods. However, low protein solubility remains a challenge, addressed by protein modification techniques (physical, chemical, and biological) to broaden its applications. Duckweed proteins hold potential as functional food ingredients due to their unique physicochemical properties. This re view also includes patents and regulations related to duckweed protein, filling a gap in current literature. Overall, duckweed presents a sustainable protein source with a lower environmental impact compared to con ventional crops.